2014
DOI: 10.1128/mcb.00230-14
|View full text |Cite
|
Sign up to set email alerts
|

Specific α-Arrestins Negatively Regulate Saccharomyces cerevisiae Pheromone Response by Down-Modulating the G-Protein-Coupled Receptor Ste2

Abstract: e G-protein-coupled receptors (GPCRs) are integral membrane proteins that initiate responses to extracellular stimuli by mediating ligand-dependent activation of cognate heterotrimeric G proteins. In yeast, occupancy of GPCR Ste2 by peptide pheromone ␣-factor initiates signaling by releasing a stimulatory G␤␥ complex (Ste4-Ste18) from its inhibitory G␣ subunit (Gpa1). Prolonged pathway stimulation is detrimental, and feedback mechanisms have evolved that act at the receptor level to limit the duration of signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
160
2
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(186 citation statements)
references
References 164 publications
(215 reference statements)
15
160
2
9
Order By: Relevance
“…In the yeast Saccharomyces cerevisiae, ubiquitylation of cell surface proteins is mediated by the HECT family Rsp5 Ub ligase. More recent analysis of several yeast plasma membrane permeases and receptors has shown that arrestin-like adaptors named Art (for arrestin-related trafficking) are essential to recruiting Rsp5 to these proteins (3)(4)(5).…”
mentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, ubiquitylation of cell surface proteins is mediated by the HECT family Rsp5 Ub ligase. More recent analysis of several yeast plasma membrane permeases and receptors has shown that arrestin-like adaptors named Art (for arrestin-related trafficking) are essential to recruiting Rsp5 to these proteins (3)(4)(5).…”
mentioning
confidence: 99%
“…Will yeast arrestins be linked to alternate Ste2p receptor functionalites, as is the case in mammalian systems? Although this remains to be tested, a recent report has highlighted roles for arrestin-like proteins in Ste2p desensitization (17), setting the stage for possible roles for arrestins in mediating Ste2p-linked signalling pathways downstream of classical MAPK signalling. Overall, possible continued relevance of the yeast pheromone-mating pathway as a simplified model for GPCR research, in the broader context of alternate functionalities for GPCRs, is supported based on validation of alternate functionalities for Ste2p in modulation of mating events.…”
Section: Resultsmentioning
confidence: 99%
“…However, now, the possibility of biased signalling for the yeast pheromone receptors cannot be ignored. This is particularly true in light of the recent demonstration of a direct interaction between a-arrestins and Ste2p in internalization events (17).…”
mentioning
confidence: 96%
“…Most recently, this was demonstrated for Ste2p, with Art1 (Ldb19), Art4 (Rod1) and Art7 (Rog3) all being implicated in modulation of receptor internalization (Alvaro et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…While direct evidence is still lacking due to difficulties addressing the redundancy associated with a single receptor mediating two temporally distinct steps in the same process, the possibility of alternate GPCR-linked signaling in yeast can no longer be ignored. This is particularly true in light of the recent demonstration of a direct interaction between yeast arrestin-like proteins and Ste2p in internalization events (Alvaro et al, 2014). A family of 10 arrestin-like proteins, termed -arrestins is known to be expressed in S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%